Systematic Review: A Study of College Adjustment Among First-Year Undergraduates - Hesti Purnamasari; Farida Kurniawati; Tjut Rifameutia (Faculty of Psychology Universitas Gadjah Mada, 2022)
College adjustment is an important factor that influences academic success. First-year undergraduates must deal with a transition period from high school to college, during which time they encounter many challenges which can result in high dropout rates and low academic outcomes. This transition period requires adaptability. A systematic review was conducted to gain an overview of college adjustment and its influence. Using five online research platforms, namely EBSCOhost, PsycNet, Science Direct, Scopus, and Taylor & Francis Online, 18 articles were obtained. As a result, college adjustment can be characterized by indicators such as academic achievement, stress, anxiety, depression, and well-being. The Attachment Theory and Self-determination Theory were applied in more than one study. Individual and environmental characteristics can influence college adjustment, both positively as well as negatively. Recommendations for research on the topic of college adjustment are being discussed.